Language learning in new English contexts studies of acquisition and development - Silver, Rita E.; Goh, Christine Chuen Meng; Alsagoff, Lubna (Continuum, 2009)
Examines economic, social and political factors influencing language education, and presents a global perspective on English language acquisition. This book explores English language acquisition and development outside of the largely monolingual environments of North America, the United Kingdom and Australia